Management of Children’s Faecal Matter and Its Implications for Cholera Outbreak in the Cape Coast Metropolis - Animah, P. (University of Ghana, 2018)
Ghana as a country is faced with series of sanitation problems, especially in the area of human faecal management. Improper handling and disposal of faecal waste has resulted in the outbreak and spread of diseases such as Cholera. Cape Coast Metropolis, which houses the capital of the Central Region of Ghana, faces such challenges as lack of toilets in various households, poor sanitation and crowded areas. Disposal of children’s faeces has therefore become an area of concern in the Metropolis since mothers and other child caregivers resort to indiscriminate and untraditional methods of children feces disposal due to lack of improved toilet or latrine, which can become a vehicle for the outbreak and spread of Cholera. The study sought to assess disposal of children’s faecal matter in households and how it contributes to Cholera outbreak within the Cape Coast Metropolis. The study employed the mixed methods research approach and employed both primary and secondary data. A Multi stage sampling method was used to select the population for the study and stratified sampling was used to group the Metropolis into three, based on income level. The purposive and simple random sampling methods were used to select one community each from each stratum. 331 respondents were used for the study. This included 300 households, 10 opinion leaders, and 21 women for focus group discussion. Data was coded and analyzed with SPSS, where descriptive statistics such as frequencies, percentages, chi square and regression were employed to explain the differences, relationships and association between variables. The study revealed households with unsafe children’s faecal matter disposal to be at high risk of getting Cholera, but the relationship was not significant. However, it was statistically proven that households who bought food outside were at higher risk of getting cholera. It is therefore recommended that Food and Drugs Board Authority together with Standard Authority ensure food vendors get the necessary permit before selling any food. And there should be a constant check up on food vendors concerning containers for selling food, environment in which food is sold and personal hygiene of these vendor.
MPhil.
Keywords: Human Faecal Management; Cholera; Cape Coast Metropolis